PEMERTAHANAN LEKSIKON DAN MAKNA KULTURAL MOTIF BATIK KEBUMEN SEBAGAI UPAYA PRESERVASI WARISAN BUDAYA BANGSA - Yuli Kristianingsih; Nur Faidah; Yulia Cahyani (Universitas Sebelas Maret, 2021)
Kebumen batik is not as widely known as batik from Jogja, Surakarta, and Pekalongan. This is due to several factors, such as marketing, age, and production imbalances. One way to preserve Kebumen batik is by describe and maintain lexicons and cultural meanings contained in batik in Gemeksekti Village, Kebumen Regency. Gemeksekti Village is one of the batik centers in Kebumen which has been named the village of Kebumen batik. The method used in writing this article is a descriptive qualitative method with literature review techniques. Based on the data obtained, there were 143 batik lexicons. The lexicons were 64 batik lexicons based on tools and materials, 31 batik lexicons based on the batik process, 48 batik lexicons based on motives. Batik motifs in Kebumen not only have philosophical value, but their depiction is also based on artistic value. Cultural values from several Kebumen batik motifs can be found in gringsing, sirikit, limaran, and ukel motifs. The lexicon findings can be made in to dictionaries and books containing batik motifs, explanation of motifs, pictures, and the history of Kebumen batik and other media. Both of them may be used as a means for introduction to the wider community and the preservation of Kebumen batik.